Landscape, space and place in English- and German-language poetry 1960-1975 - Thomas, Nicola (2017)
This thesis examines representations of space, place and landscape in English and German-language poetry of the period 1960-1975, a key transitional phase between modernity and postmodernity. It proposes that the impact certain transnational spatial revolutions had on contemporary poetry can only be fully grasped with recourse to comparative methodologies which look across national borders.